2021
DOI: 10.1371/journal.pone.0247111
|View full text |Cite
|
Sign up to set email alerts
|

Decadal (2006-2018) dynamics of Southwestern Atlantic’s largest turbid zone reefs

Abstract: Tropical reefs are declining rapidly due to climate changes and local stressors such as water quality deterioration and overfishing. The so-called marginal reefs sustain significant coral cover and growth but are dominated by fewer species adapted to suboptimal conditions to most coral species. However, the dynamics of marginal systems may diverge from that of the archetypical oligotrophic tropical reefs, and it is unclear whether they are more or less susceptible to anthropogenic stress. Here, we present the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 84 publications
0
17
0
Order By: Relevance
“…Variable toxicity within the same BCMs that we observed (i.e., 3 out of 11 samples caused >50% mortality) should not imply a lack of chemical defense by cyanobacteria, as spatial and seasonal variability of chemical defenses against herbivores is expected due to metabolic responses to changes in the environment (Puglisi et al, 2019). The high spatial variability of Abrolhos reefs likely contributes to a context dependency of BCMs toxicity (Ribeiro et al, 2018;Teixeira et al, 2021). The large biomass of morbid sea slugs, Stilocheylus striatus, observed during cyanobacterial blooms in Abrolhos reefs (Ribeiro et al, 2017) is in line with the toxic potential of Abrolhos BCMs observed here.…”
Section: Benthic Cyanobacterial Mat Toxicity and Susceptibility To Consumersmentioning
confidence: 67%
See 2 more Smart Citations
“…Variable toxicity within the same BCMs that we observed (i.e., 3 out of 11 samples caused >50% mortality) should not imply a lack of chemical defense by cyanobacteria, as spatial and seasonal variability of chemical defenses against herbivores is expected due to metabolic responses to changes in the environment (Puglisi et al, 2019). The high spatial variability of Abrolhos reefs likely contributes to a context dependency of BCMs toxicity (Ribeiro et al, 2018;Teixeira et al, 2021). The large biomass of morbid sea slugs, Stilocheylus striatus, observed during cyanobacterial blooms in Abrolhos reefs (Ribeiro et al, 2017) is in line with the toxic potential of Abrolhos BCMs observed here.…”
Section: Benthic Cyanobacterial Mat Toxicity and Susceptibility To Consumersmentioning
confidence: 67%
“…Throughout the text samples, PLES and PAB will be referred to as PLES BCM and PAB BCM , respectively. The BCMs cover and long-term survey data are described in Teixeira et al (2021). An aliquot of each sample was rinsed with filtered (GF/F) seawater and snap-frozen or fixed in 1% glutaraldehyde.…”
Section: Sampling and Establishment Of Cyanobacterial Culturesmentioning
confidence: 99%
See 1 more Smart Citation
“…Divers and reef scientists noticed coral declines more frequently than fishers probably because they are more likely to pay attention to the reef substrate and sessile invertebrates due to their recreational and scientific interest, respectively (Giglio et al, 2015). This perception is corroborated by the increase in coral mortality due to more frequent and intense thermal anomalies in addition to land-based stressors in Brazil (Teixeira et al, 2021). Reef scientists were also the only stakeholder group to notice a decline in sea urchin populations.…”
Section: Discussionmentioning
confidence: 99%
“…Reef ecosystems are one of the most diverse environments on Earth, commonly known to flourish in tropical areas (Spalding et al 2001). Although the development of coral reefs and, thus, the production of a biogenic carbonate framework can be limited by abiotic factors such as temperature and light penetration, coral communities still thrive in a range of environmental settings (Kleypas et al 1999;Perry and Larcombe 2003).…”
Section: Introductionmentioning
confidence: 99%